Optical solitons of the Kudryashov Equation via an analytical technique - Raheel, M.; İnç, Mustafa; Tala-Tebue, E.; Bayram, Mustafa (Springer, 2022)
Some new optical solitons find for the Kudryashov equation (KE) in this study. These solutions are in the form of dark, bright, singular, singular-dark solitons and other solutions with certain conditions. These new solutions may be applied in the demonstration of Kudryashov equation in some better way. Modified integration method, the extended Sinh-Gordon equation expansion method (ShGEEM) is utilized to secure the aforesaid solutions. The results are also verified with the use of Mathematica symbolic programming software. These optical solitons suggest that this method is effective and straight forward compared to other methods and the results are reliable. The obtained solutions are very helpful in the field of optical fibers.
Keywords: Kudryashov equation; ShGEEM; Optical soliton